Alternative solution to achieve abnormal returns on the Indonesian Stock Exchange - Triadji, Iwan; Busnetty, Ida; Sihombing, Pardomuan (Goodwood Publishing, 2024)
Purpose: Investors continuously achieve abnormal returns (ARs) by adopting advanced strategies. Therefore, this study aimed to compare the performance of the IDX Value30 and IDX Growth30 indices, which represent value and growth investment strategies in Indonesia. Method: The comparison in this study was conducted using return- and risk-adjusted variables represented by Information Ratios and Jensen’s alpha. Based on this approach, Mann-Whitney and independent sample t-tests were performed using the SPSS program. Results: Both the IDX Value30 and IDX Growth30 indices show positive abnormal returns. However, a comparison of returns, Information Ratios, and Jensen's alpha showed no significant differences between the IDX Value30 and IDX Growth30. Limitations: The secondary data of IDX Value30 and IDX Growth30 indices were limited to the period from January 30, 2014, to September 30, 2022. Contribution: IDX Value30 and IDX Growth30 could serve as references for investors and Investment Managers in executing value- and growth-investing strategies to outperform IHSG. Furthermore, Investment Managers could use these indices as benchmarks for issuing index funds or ETFs. Novelty: This study uniquely compares the performance of value and growth investing using the IDX Value30 and IDX Growth30 indices, a comparison that has not been previously conducted.